Clonal Propagation of Khaya senegalensis: The Effects of Stem Length, Leaf Area, Auxins, Smoke Solution, and Stockplant Age - Catherine Ky-Dembele; Mulualem Tigabu; Jules Bayala; Patrice Savadogo; Issaka Joseph Boussim; Per Christer Odén (International Journal of Forestry Research)
Khaya senegalensis is a multipurpose African timber species. The development of clonal propagation could improve plantation establishment, which is currently impeded by mahogany shoot borer. To examine its potential for clonal propagation, the effects of cutting length, leaf area, stockplant maturation, auxin, and smoke solution treatments were investigated. Leafy cuttings rooted well (up to 80%) compared to leafless cuttings (0%). Cuttings taken from seedlings rooted well (at least 95%), but cuttings obtained from older trees rooted poorly (5% maximum). The rooting ability of cuttings collected from older trees was improved (16% maximum) by pollarding. Auxin application enhanced root length and the number of roots while smoke solution did not improve cuttings' rooting ability. These results indicate that juvenile K. senegalensis is amenable to clonal propagation, but further work is required to improve the rooting of cuttings from mature trees.